2015
DOI: 10.1108/arla-10-2014-0165
|View full text |Cite
|
Sign up to set email alerts
|

Self-employment as a moderator between work and life satisfaction

Abstract: Purpose The correlation between work and life satisfaction varies substantially across studies, suggesting that the strength of the relationship may depend on the studied population and its circumstances. The purpose of this paper is to assess the strength of the relationship in the context of Chile and the moderator effect of self-employment (SE), whether a worker is self-employed or on a salary. Design/methodology/approach Based on the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 73 publications
3
17
0
2
Order By: Relevance
“…In this regard, there is evidence showing a negative relationship between the job domain and overall life satisfaction [ 44 ] and even showing a lack of relationship between them [ 45 ]. Nevertheless, consistent with the positive outcome highlighted by Edralin [ 43 ], several studies support a positive relationship between job satisfaction and overall life satisfaction at an individual level in workers in different countries [ 5 , 6 , 11 , 41 , 42 , 46 , 47 ].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this regard, there is evidence showing a negative relationship between the job domain and overall life satisfaction [ 44 ] and even showing a lack of relationship between them [ 45 ]. Nevertheless, consistent with the positive outcome highlighted by Edralin [ 43 ], several studies support a positive relationship between job satisfaction and overall life satisfaction at an individual level in workers in different countries [ 5 , 6 , 11 , 41 , 42 , 46 , 47 ].…”
Section: Introductionsupporting
confidence: 66%
“…Job satisfaction is traditionally defined by how employees feel and think about their work [ 11 ], which includes measuring individuals’ emotional states, affective responses and cognitive evaluations of work [ 40 ]. Different authors have suggested that the job domain determines the level of life satisfaction, given that work is one of the most important parts of an individual’s life and takes a large share of their time [ 41 , 42 ]. However, Edralin [ 43 ] stressed that this relationship can result in positive and negative outcomes, which in turn may lead to elevated satisfaction levels in some individuals and stress in others.…”
Section: Introductionmentioning
confidence: 99%
“…Life satisfaction as a general indicator is positively related to satisfaction with domains such as work, family or leisure time (Bowling, Eschleman, & Wang, 2010). For entrepreneurs, job satisfaction is more closely related to satisfaction with life, family and self than it is for employees, reflecting the centrality of work in their life (Loewe, Araya-Castillo, Thieme, & Batista-Foguet, 2015;Thompson, Kopelman, & Schriesheim, 1992).…”
Section: Mental Health and Well-beingmentioning
confidence: 99%
“…Work is a central dimension of satisfaction in the lives of individuals, given the amount of time and energy invested in it and its importance for generating positive social relationships, commanding respect in society and forging a sense of belonging and identity. In addition, the relationship between job and life satisfaction is positive, especially among self-employed workers (Loewe, Araya-Castillo, Thieme, & Batista-Foguet, 2015).…”
Section: Job Satisfactionmentioning
confidence: 99%